Clitoria ternatea L (Butterfly Pea) Making Education in Banangkah Village (Benangkah), Burneh District, Bangkalan, East Java - A. Endang Kusuma Intan; Siti Solihah; Sakinah Qurrotul Aini; Teguh Setiawan Wibowo (Jurnal Pengabdian Masyarakat Formosa, 2023)
Among the numerous scientific publications that affirm the advantages of butterfly pea blossoms. The inhabitants of Benangka Village, Burneh District, Bangkalan City, among others, do not appear to be familiar with this information to a large extent, according to community facts. Despite the fact that they have a butterfly plant in their yard. Based on this, we believe it is essential to hold educational activities for the residents of Benangka Village regarding the potential and benefits of the butterfly pea flower as well as suitable processing techniques, in order for the benefits of the butterfly pea flower to be felt by the larger community as fully as possible. The method used in this PKM activity was socialization and a demonstration of how to make butterfly pea flower herbal drink using a simple technique, namely brewing. The community responded positively to the activities that were carried out, as evidenced by the enthusiasm displayed during the activity.